Dal sintomo al sinthomo. Psicoanalisi e incarnazione - Cimatti, Felice (Dialogoi. Rivista di studi comparatistici, 2020)
In this paper the psychoanalytic process is described as an incarnation process. The objective of the analysis is to pass from a spoken body to an incarnated body: in Lacanian terms from the symptom body to the “sinthome” body.